MENINGKATKAN KEMAMPUAN MEMAKAI SERAGAM SEKOLAH MELALUI MEDIA MODEL BAGI ANAK TUNAGRAHITA RINGAN - Lita - Susanti (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background by mild mental retardation issue has not been able to dress, clothes are often out of the pants, shirt buttons apart from the hole, zipper pants that often is partnered so that children feel embarrassed and feel less confident then be made to improve the child's ability to install and off school uniform by using the model. This study aims to improve children's school uniforms through the media model.